Kepuasan Karyawan di RSUD DR. Soedomo Trenggalek Tahun 2024 - Setyarini, Endah; Sukadiono, Sukadiono; Wiliyanarti, Pipit Festi (Journal of Telenursing (JOTING), 2025)
This study aims to examine team member satisfaction at RSUD Dr. Soedomo Trenggalek, highlighting its importance in the hospital's success and the quality of service. The method used was a quantitative survey approach, which 145 employees analyzed. The study's results showed high satisfaction with the work environment and team member relations, but there were varying responses regarding compensation and career development. Although most employees were satisfied with their workload, some expressed dissatisfaction, indicating problems in task management. In conclusion, decision-making policies require more attention, with many employees feeling neutral or dissatisfied. Keywords: Employee Satisfaction, Compensation, Work Environment, Hospital Management, Career Development